2016
DOI: 10.1080/09500693.2016.1145368
|View full text |Cite
|
Sign up to set email alerts
|

‘Risky fun’ or ‘Authentic science’? How teachers’ beliefs influence their practice during a professional development programme on outdoor learning

Abstract: Teaching outdoors has been established as an important pedagogical strategy, however science classes rarely take place outside. Previous research has identified characteristics of teachers who have integrated out-of-classroom opportunities into their teaching repertoire, yet little is understood as to why teachers make these different pedagogical decisions. This paper explores the relationship between secondary science teachers' beliefs and their pedagogical practice during a two-year professional development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 39 publications
1
50
0
5
Order By: Relevance
“…Numerous challenges to outdoor science teaching were indeed identified as specific to these levels, but ways to overcome them unfortunately remain largely unclear. As Glackin (2016) suggested, such research studies might be crucial in the development of effective training programs for pre-service and in-service teachers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous challenges to outdoor science teaching were indeed identified as specific to these levels, but ways to overcome them unfortunately remain largely unclear. As Glackin (2016) suggested, such research studies might be crucial in the development of effective training programs for pre-service and in-service teachers.…”
Section: Resultsmentioning
confidence: 99%
“…For example, scientists need to go outside in order to study habitats, the effects of changing seasons on plants, or the effects of urban heat islands on human health. Paradoxically, science education at school generally happens indoors; it is only on rare occasions that it unfolds outside (Glackin, 2013(Glackin, , 2016Rickinson et al, 2004). This might at least partly explain why many authors claim that more connections with real-life settings should be established to counterbalance the frequently reported and denounced lack of authenticity at school (Bencze & Hodson, 1999;Braund & Reiss, 2006;Fägerstam, 2014;Gafoor & Narayan, 2012;Krapp & Prenzel, 2011;Potvin, & Hasni 2014;Rivet & Krajcik, 2008;Smith, 2013;Tal, Alon, & Morag, 2014).…”
Section: Science Education and Learning Outdoorsmentioning
confidence: 99%
“…Furthermore, teachers who are reported to have high teacher self-efficacy use a variety of teaching methods (Cantrell & Callaway 2008), are less reliant on curriculum guides and emphasise cross-curriculum links during teaching (De Laat & Watters 1995). Such teachers often emphasise problem-solving and logical thinking through 'real life' 4 examples valuing the 'unique' opportunities for student autonomy rather than viewing real life example solely as fun (Czerniak & Schriver 1994;De Laat & Watters 1995;Glackin 2016).…”
Section: Understanding Self-efficacymentioning
confidence: 99%
“…See Glackin (2016) for an extended account of the professional development guiding principles, the content, the design of the professional development programme and the research design. The programme team included of one of the paper's authors (Glackin) who was a programme tutor, programme developer, as well as a researcher.…”
Section: Study Contextmentioning
confidence: 99%
“…Therefore, studies of teacher PD that focus on teacher learning communities require a higher level of participation than merely joining in CoP activities (Grossman et al, 2001;Jones et al, 2013). However, when teachers collaborate with their colleagues to achieve common goals, occasionally the relationship between them can become tense because of conflicting individual beliefs on teaching practice (Dooner, Mandzuk, & Clifton, 2008;Glackin, 2016;So, 2013). Teledahl (2015) reported that teachers can arrive at different evaluations of the same students' work because they have different content knowledge.…”
Section: Communities Of Practicementioning
confidence: 99%